2017
DOI: 10.1371/journal.pone.0182243
|View full text |Cite
|
Sign up to set email alerts
|

De novo leaf and root transcriptome analysis to identify putative genes involved in triterpenoid saponins biosynthesis in Hedera helix L.

Abstract: Hedera helix L. is an important traditional medicinal plant in Europe. The main active components are triterpenoid saponins, but none of the potential enzymes involved in triterpenoid saponins biosynthesis have been discovered and annotated. Here is reported the first study of global transcriptome analyses using the Illumina HiSeq™ 2500 platform for H. helix. In total, over 24 million clean reads were produced and 96,333 unigenes were assembled, with an average length of 1385 nt; more than 79,085 unigenes had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…After the assembly and annotation of the A. elata transcriptome in the present study, we were able to begin examining the terpenoid biosynthesis backbone and sesquiterpenoid and triterpenoid biosynthesis pathways in these samples, leading to the identification of 19 functional genes. While these two pathways are well-known to be important for the biosynthesis of terpenoids and sterols in P. notoginseng [22] and Hedera helix L. [23], the results of the present analysis are the first such comprehensive analysis of these pathways in A. elata. Triterpenoids and sesquiterpenoids are biosynthesized via the MVA pathway, that takes place primarily in the cytoplasm, whereas monoterpenoids, diterpenoid, and tetraterpenoids are biosynthesized via the MEP pathway, mostly in the plastid [11].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…After the assembly and annotation of the A. elata transcriptome in the present study, we were able to begin examining the terpenoid biosynthesis backbone and sesquiterpenoid and triterpenoid biosynthesis pathways in these samples, leading to the identification of 19 functional genes. While these two pathways are well-known to be important for the biosynthesis of terpenoids and sterols in P. notoginseng [22] and Hedera helix L. [23], the results of the present analysis are the first such comprehensive analysis of these pathways in A. elata. Triterpenoids and sesquiterpenoids are biosynthesized via the MVA pathway, that takes place primarily in the cytoplasm, whereas monoterpenoids, diterpenoid, and tetraterpenoids are biosynthesized via the MEP pathway, mostly in the plastid [11].…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, 28 unigenes encoding 4 putative enzymes (FPS, SS, SE, and bAS) were found to be associated with carbocyclic biosynthesis (Additional file 3: Table S1). For the majority of these genes, we were able to map >1 unigene to a given gene or gene family (Additional file 3: Table S1), suggesting that these sequences may correspond to multiple copies or partial fragments of a given gene [23]. In each of enzymatic steps, those unigenes that were showed a high identity with functionally characterized genes and differentially expressed in different tissues were next selected and arranged into a heat map.…”
Section: Enrichment Of Terpenoid Backbone and Triterpenoid Biosynthetmentioning
confidence: 99%
“…It was found that the content of triterpenes accumulated in the leaves of P. ginseng are higher in the early growth stage, while the content of triterpenes in the roots of old plants are higher [27]. Comparative transcriptome analysis including root and leaf tissues to excavate transcripts related to saponin biosynthesis is already reported for many plants, such as Hedera helix [28], Panax notoginseng [29] and Asparagus racemosus [26]. The maximum triterpenoid saponin content was identi ed in stem.…”
Section: Introductionmentioning
confidence: 85%
“…Total RNA from the mixed sample (three individual plants) was isolated using the RNA EasySpin Isolation System (Aidlab Biotech, Beijing, China) according to the manufacturer's protocol. Following treatment with RNase-free DNase I (New England BioLabs) for 30 min at 37 • C to remove residual DNA, sequencing was performed by Shanghai Biotechnology Co. Ltd., where a cDNA library was constructed and subjected to Illumina HiSeq2500 sequencing, as described by Sun et al [35].…”
Section: Cdna Library Preparation and Illumina Transcriptomic Sequencingmentioning
confidence: 99%